SOME INDICES OF METABOLISM IN CHILDREN WITH IRRITABLE BOWEL SYNDROME AND CO-EXISTING OVERWEIGHT - Lembryk, I.S.; Zhyliak, O.V.; Tsytsyura, O.O.; Shlimkevych, I.V.; Dutchuk, O.V.; Buyak, P.Z.; Stefanyshyn, A.B. (World of Medicine and Biology, 2023)
In this article, we demonstrate the data on clinical course features of irritable bowel syndrome in children of school age with normal weight as well as co-existing overweight. Also, we conducted an assessment of certain indices of lipid and carbohydrate metabolism in these conditions. Clinical features of irritable bowel syndrome with overweight include duration of the disease (6.5±0.5 months), female sex (30 vs. 5 children, χ2=5.1429, p
Keywords: children; irritable bowel syndrome; overweight; faecal calprotectin